2021
DOI: 10.1002/cam4.4188
|View full text |Cite|
|
Sign up to set email alerts
|

Fat mass and obesity‐associated protein regulates tumorigenesis of arecoline‐promoted human oral carcinoma

Abstract: This is an open access article under the terms of the Creat ive Commo ns Attri bution License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
39
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 28 publications
(40 citation statements)
references
References 32 publications
1
39
0
Order By: Relevance
“…Our previous study demonstrated that chronic low‐dose arecoline‐treated OSCC cell lines (hereinafter referred to as CAL27‐A and SCC25‐A) exhibit superior tumorigenic effects to original OSCC cell lines (CAL27 and SCC25), and FTO plays a vital role in chronic arecoline‐exposure‐promoted oncogenicity of OSCC cells. 21 To elucidate the potential molecular mechanism underlying arecoline‐promoted oral cancer malignance, we conducted an RNA‐seq transcriptome assay using CAL27‐A and CAL27 cells. A total of 188 genes and 370 genes were significantly ( P < 0.05 and fold change >2 or <0.5) upregulated and downregulated in arecoline‐treated CAL27 (CAL27‐A) compared to CAL27, respectively (Figure 1A ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Our previous study demonstrated that chronic low‐dose arecoline‐treated OSCC cell lines (hereinafter referred to as CAL27‐A and SCC25‐A) exhibit superior tumorigenic effects to original OSCC cell lines (CAL27 and SCC25), and FTO plays a vital role in chronic arecoline‐exposure‐promoted oncogenicity of OSCC cells. 21 To elucidate the potential molecular mechanism underlying arecoline‐promoted oral cancer malignance, we conducted an RNA‐seq transcriptome assay using CAL27‐A and CAL27 cells. A total of 188 genes and 370 genes were significantly ( P < 0.05 and fold change >2 or <0.5) upregulated and downregulated in arecoline‐treated CAL27 (CAL27‐A) compared to CAL27, respectively (Figure 1A ).…”
Section: Resultsmentioning
confidence: 99%
“…Several FTO inhibitors, such as R-2-hydroxyglutarate (R-2HG), FB23, and FB23-2, exert potent anti-leukemic activity both in vitro and in vivo. 19,20 In a previous study, we described how FTO upregulation is pivotal for arecoline-treated OSCC acquiring malignant phenotypes, 21 but the underlying molecular mechanism is unknown. In the current study, we aim to identify the critical mRNA target of FTO and to explore a potential targeted therapy to treat arecoline-induced OSCC.…”
mentioning
confidence: 99%
“…First, it oxidizes m 6 A to N6-hydroxymethyl adenosine (Hm 6 A), then converts Hm 6 A to N6-formyl adenosine (F 6 A) and ultimately converts F 6 A to adenosine to finalize the m 6 A demethylation process (16). Studies have indicated that FTO is involved in autophagy, cell proliferation and chemotherapy resistance (59)(60)(61). Furthermore, ALKBH5 has been closely associated with chemotherapy resistance (62).…”
Section: Rna Modification and M 6 Amentioning
confidence: 99%
“…Furthermore, FTO upregulation in oral squamous cell carcinoma causes further tumor progression, whereas FTO downregulation remarkably represses tumor cell proliferation, colony formation and tumor growth (Li et al, 2021a). The in vivo assays in mice indicated that FTO knockdown slows down tumor growth (Li et al, 2021b). Subsequently, FTO might act as an effective therapeutic target against OSCC.…”
Section: Oral Squamous Cell Carcinomamentioning
confidence: 99%